Spatiotemporal Variation in Fractional Vegetation Coverage and Quantitative Analysis of Its Driving Forces: A Case Study in the Tabu River Basin, Northern China, 1986–2023 - Zihe Wang; Yangwen Jia; Cunwen Niu; Jiajia Liu; Jing Jin; Zilong Liao; Mingxin Wang; Guohua Li; Jing Zhang (Remote Sensing, 2025)
The Tabu River Basin (TRB) is one of the most ecologically fragile areas in the arid regions of northern China; it is a key component of the desert steppe north of the Yinshan Mountains. The fractional vegetation coverage (FVC) represents a vital indicator of ecological health in the TRB. In this study, we explored the impacts of climate change and human activities on vegetation growth and utilized Landsat data (30 m) from the Google Earth Engine to generate a long-term FVC dataset (1986–2023) in the TRB. Furthermore, we established a framework for quantitatively identifying the effects of climate change and anthropogenic activities on the FVC in desert steppe regions. The results revealed that: (1) the FVC exhibits considerable spatial heterogeneity, with higher values observed in the southeastern and southwestern areas and lower values in the northern part; (2) over the past 38 years, the annual average FVC has shown fluctuations, with a slight declining trend, while the Hurst exponent indicates a reverse persistence pattern in the FVC across the TRB; and (3) the correlation between the FVC and the temperature is marginally stronger than that with precipitation, and the influence of climate change on promoting the FVC outweighs the role of human activities. These results offer valuable insights for ecological restoration and sustainable development efforts and provide scientific support for monitoring vegetation in the region.